The Judicial Commission and Institutional Challenges in the Appointment of Judges in Indonesia’s Reform Framework - Ulum, Muhammad Bahrul (Journal of Judicial Review, 2025)
This paper critically examines the position of the Judicial Commission within Indonesia's post-reform judicial structure, focusing on its constitutional mandate established through the 1999–2002 constitutional amendments. Although initially designed as an independent supervisory body tasked with overseeing judicial behaviour and ethics, the Commission's constitutional authority has been significantly constrained by the legal resistance from the Supreme Court, particularly through lawsuits brought before the Constitutional Court. Central to this study is the Judicial Positions Bill (RUU Jabatan Hakim), which reimagines the procedure of judicial appointments through a collaborative framework between the Supreme Court and the Judicial Commission to encourage judicial independence, accountability, and integrity through a transparent and merit-based selection process. Using a socio-legal and comparative approach, the study advocates for a more inclusive and participatory approach to judicial selection by incorporating public engagements such as civil society, experts, and professionals. The findings highlight the need to strengthen the Judicial Commission’s role, emphasising that its involvement in the recruitment process is crucial to tackling judicial corruption and enhancing the integrity of Indonesia’s judiciary. This study contributes to the broader discussion on judicial reform in the Global South, emphasising the importance of integrating institutional frameworks with accountability.